Using Google Classroom to Increase Student Motivation in a Pandemic Period - Warih Setya Wardani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to increase the learning motivation of students in class VI Theme 5. This research is a classroom action research (CAR) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 37 students of class VI SD Negeri 1 Purwanegara in the 2020/2021 academic year. Data collection techniques using observation and questionnaires. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of Google Classroom in online learning during a pandemic can increase student learning motivation Theme 5 class VI SD Negeri 1 Purwanegara academic year 2020/2021 as evidenced by the percentage increase in learning motivation in cycle I by 65% to 84% in cycle II and increasing in cycle III by 95%.